Dual-mode index modulation aided OFDM with generalized prefix - Aldırmaz Çolak, Sultan; Cooklev, Todor; ACAR, YUSUF (My University, 2019)
Recently, a dual-mode OFDM relying on index modulation (DM-OFDM-IM) has been introduced to increase the data rate of the conventional IM based OFDM techniques. However, such a mechanism has bit error rate performance loss due to the deep fading channels such as the practical Rayleigh channels. In this work, to improve the BER performance of the DM-OFDM-IM technique, a new technique, that is called as DM-OFDM-IM with generalized prefix (DM-OFDM-IM-GP) is proposed. The simulation results illustrate that the proposed DM-OFDM-IM with GP achieves about 10 dB SNR gain over the existing DM-OFDM-IM at the spectral efficiency of 4, 2.22 and 1.33 bits/s/Hz in Rayleigh fading channel. Keywords-Index Modulation; Generalized Prefix; Orthogonal Frequency Division Multiplexing; Dual-Mode, Index Modulation, Spatial Modulation.